APPLICATION OF THE ECONOMIC ORDER QUANTITY METHOD FOR OPTIMIZATION OF SUPPLAY CHAIN MANAGEMENT IN CONTROLLING PRODUCT INVENTORY - Abulwafa Muhammad; Wega Andre; Teri Ade Putra (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Toko Sri Bunga is an electronic store that obtains products from various suppliers then sells and delivers these products to consumers. The existing supplier and consumer management processes are conventional. This raises several problems related to product inventory, minimum product stock determination, and high inventory costs. The purpose of this research is to optimize supply chain management (SCM) in inventory control at Sri Bunga shops using the Economic Order Quantity (EOQ) method. This method is used to get the most optimal calculation of the number of orders, inventory and storage costs. The results of this study based on the calculation of the EOQ method on one sample of LG 24 TL 520V-PT TV products for 6 months obtained optimal results for ordering 36 product units with a total inventory cost of IDR 1,014,935. The results of this study can be used as a reference for the development of SCM applications used in supplier and consumer management